Makna Hijrah dalam Konstruksi Media Massa - Robiah Al Adawiyah; Kamila Adnani (Academic Journal of Da'wa and Communication, 2021)
This study aims to describe the representation of hijrah in the Q&A program of "Hijrah Berjamaah" episode on Youtube Q&A Metro TV. The background of this study was the rise of religious phenomena, especially the phenomenon of hijrah that occured in society, where many people misused the term hijrah so that there was a shift in the meaning of hijrah itself. The Q&A Metro TV talk show program of "Hijrah Berjamaah" episode aims to straighten out the meaning of hijrah from various points of view. The researcher chose the show on the episode of Husein Ja'far Al-Hadar as the speaker because besides being a habib, he was also close to young people. This study used a qualitative descriptive method with the representation theory of Stuart Hall. This study was conducted by observing and documenting toward the reruns of the Q&A Metro TV program of "Hijrah Berjamaah" episode on Youtube Q&A Metro TV. The validity of the study data used was the source triangulation technique complemented by the interactive data analysis. The results of this study stated: first, hijrah is a journey from darkness to light or from bad to good. The substance of hijrah is the heart; second, it is not permissible to do hijrah with the aim of trading its hijrah. This is because the hijrah must be solely because of Allah and the standard of hijrah itself is moral; third, the representation of the current hijrah is spiritual hijrah, cultural hijrah, intellectual hijrah, and social hijrah.